Neutron star masses in R-2-gravity - Sbisá, Fulvio; Baqui, Pedro O.; Miranda, Tays; Piattella, Oliver F. (Physics of the Dark Universe, 2020)
We address the issue of the existence of inequivalent definitions of gravitational mass in R-2-gravity. We present several definitions of gravitational mass, and discuss the formal relations between them. We then consider the concrete case of a static and spherically symmetric neutron star, and solve numerically the equations of motion for several values of the free parameter of the model. We compare the features of the mass-radius relations obtained for each definition of gravitational mass, and we comment on their dependence on the free parameter. We then argue that R-2-gravity is a valuable proxy to discuss the existence of inequivalent definitions of gravitational mass in a generic modified gravity theory, and present some comments on the general case. (C) 2019 Elsevier B.V. All rights reserved.